A nomogram for predicting the HER2 status of circulating tumor cells and survival analysis in HER2-negative breast cancer - Yang, Yuqin; Li, Liudan; Tian, Wenjing; Qiao, Zhen; Qin, Qi; Su, Liqian; Li, Peiqiu; Chen, Weirong; Zhao, Hong (Frontiers in Oncology, 2022)
Background In breast cancer patients with HER2-negative tumors (tHER2-), HER2-positive CTCs (cHER2+) were associated with promising efficacy of HER2-targeted therapy, but controversy has persisted over its prognostic effect. We developed a model including clinicopathologic parameters/blood test variables to predict cHER2 status and evaluated the prognostic value of cHER2+ in tHER2- patients. Methods cHER2+ was detected, blood test results and clinicopathological characteristics were combined, and a nomogram was constructed to predict cHER2 status in tHER2- patients according to logistic regression analysis. The nomogram was evaluated by C-index values and calibration curve. Kaplan–Meier curves, log-rank tests, and Cox regression analyses were performed to evaluate the prognostic value of cHER2 status. Results TNM stage, white blood cells (WBCs), neutrophils (NEUs), uric acid (UA), De Ritis ratio [aspartate transaminase (AST)/alanine transaminase (ALT)], and high-density lipoprotein (HDL) were found to be associated with cHER2 status in tHER2- patients in univariate logistic regression analysis, in which UA and De Ritis ratio remained significant in multivariate logistic regression analysis. A model combining these six variables was constructed, the C-index was 0.745 (95% CI: 0.630–0.860), and the calibration curve presented a perfect predictive consistency. In survival analysis, patients of the subgroups “with cHER2+/UA-low” (p = 0.015) and “with cHER2+/De Ritis ratio – high” (p = 0.006) had a significantly decreased disease-free survival (DFS). Conclusions Our nomogram, based on TNM stage, WBC, NEU, UA, De Ritis ratio, and HDL, may excellently predict the cHER2 status of tHER2- patients. Incorporation with UA and De Ritis ratio may enhance the prognostic value of cHER2 status.